Can Spanish firms offer dual apprenticeships without making a net investment? : Empirical evidence based on ex ante simulations of different training scenarios - Mühlemann, Samuel [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2017)
"The paper aims to simulate the potential costs and benefits for Spanish firms providing dual apprenticeship training. The paper conducts simulations of 10 training occupations in six different industries in Spain. For these simulations, we combined Spanish wage data and the existing training curriculum regarding instruction times in vocational school in Spain with data from Swiss firms offering training in similar occupations. This data contains information regarding the amount of workplace training, relative apprentice productivity, and the relative importance of non-wage training costs (such as training equipment). We found that training occupation, training scenario, and firm size are important determinants of our simulations for the expected net costs of apprenticeship training in Spanish firms. Consequently, the break-even level of apprentices' wages differs significantly by training occupation and training scenario, suggesting that one prescribed apprentice wage for all sectors and occupations would be detrimental to the willingness of many firms to provide training places." (Authors' abstract, BIBB-Doku)

Ziel dieses Beitrags ist es, die potenziellen Kosten und den möglichen Nutzen einer dualen Berufsausbildung aus der Sicht spanischer Firmen für den Fall zu simulieren, dass diese in Spanien nach schweizerischem Modell ausbilden würden. Die Simulationen wurden für zehn verschiedene Berufe aus sechs verschiedenen Wirtschaftszweigen vorgenommen: der Automobilindustrie, den Banken, der chemischen Industrie, dem Detailhandel, der Hotellerie und der Olivenölproduktion. Für alle Berufe wurden die Nettokosten für drei verschiedene Ausbildungsmodelle berechnet. Modell 1 ist dem Schweizer Modell am ähnlichsten. Dabei wird von einer dreijährigen Lehre ausgegangen. Modell 2 kommt hingegen dem aktuellen spanischen Modell am nächsten und geht davon aus, dass Lernende schon einen nachobligatorischen Bildungsabschluss haben. Modell 3 ist eine Erweiterung des Modells 2 um ein Lehrjahr und um die Annahme, dass spanische Ausbildungsbetriebe im dritten Lehrjahr gleich viel formale, innerbetriebliche Ausbildung anbieten würden wie vergleichbare Schweizer Betriebe. (BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; I 2.2.1 Westeuropa; Berufsausbildung; Kosten-Nutzen-Analyse; Ausbildungskosten; Ausbildungsertrag; Bildungsexport; Schweiz; Spanien